Differentially trivial and rigid right semi-artinian rings - Artemovych, O.D. (Algebra and Discrete Mathematics, 2004)
We obtain a characterization of right semi-artinian rings which have only trivial derivations and prove that a rigid (i.e. has only the trivial ring endomorphisms) right semi-artinian ring R is a field or isomorphic to some Zpn .